MENUNTUT AKUNTABILITAS PUTUSAN PENGADILAN MELALUI PEMIDANAAN TERHADAP HAKIM - Suhariyanto, Budi (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2012)
Judiciary corruption of somejudges become the black stain of justice, than because of that public has been forced to demand accountability court rulling. The claim is becoming more and more as the filing of RUU MA, that includes a clause of punisment for the judges, and this is a reasonable question. This research is a legal normatif juridical approach, using the secondary data, than analized with qualitative juridical analysis methods. Based on the result of this research, we can concluded that a clause of punisment for tha judges (criminalizing judge) on RUU MA regulated, were not based on the principles of criminal policy. Infact, the crisis of overreach of the criminal law is what happens when the regulated repeatedly compel. Keywords: Accountability, Court, Criminality, Judge.